Clinical Core Laboratory Testing - Molinaro, Ross; McCudden, Christopher R.; Bonhomme, Marjorie; Saenger, Amy (Springer US : Imprint: Springer, 2017)
The clinical laboratory is often known as a "black box" to nurses, physicians, and surgeons, but this concise book removes the veil by covering all the pertinent aspects of the clinical laboratory. This book bridges between medicine and chemistry by offering an overview to a clinical laboratory's structure and function, the importance of laboratory utilization and test ordering, as well as pre-analytical, analytical, and post-analytical issues of importance to recognize in any clinical laboratory. An interactive FAQ and a detailed index are also available.- Resumé vydavatel
Keywords: klinické laboratoře; klinická chemie; klinické lékařství; molekulární patologie; clinical laboratories; clinical chemistry; clinical medicine; molecular pathology; elektronické knihy; sborníky; electronic books; papers of several authors